AFFIRMATIVE ACTION IN INDIA: A CRITICAL LEGAL APPRAISAL OF RESERVATION POLICY AND ITS EFFICACY IN REALIZING SOCIAL JUSTICE - Baig, Farhatulla; Mangrulkar, Suwarna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Affirmative action, known as reservation in India, remains one of the most significant tools of social engineering adopted by the Indian State to combat historical injustices and ensure equitable access to resources and opportunities. This research paper critically examines the evolution of reservation laws, the constitutional and statutory framework, and the policy implications of its implementation. It traces the jurisprudence surrounding reservations, explores emerging challenges including the demand for religious minority reservation, and assesses whether the existing model has effectively addressed social inequalities. The paper argues for a rational, evidence-based, and inclusive approach to affirmative action, balancing constitutional ideals with evolving socio-economic realities.